From fibrotic mechanisms to clinical translation: the drug therapy revolution and delivery system breakthrough in proliferative vitreoretinopathy - Chen, Zijian; Liu, Jiangying; Quan, Liao; Wu, Lingdan; Xu, Qihua (Frontiers in Immunology, 2026)
Proliferative vitreoretinopathy (PVR) is a severe fibrotic complication following ocular trauma or retinal detachment surgery, characterized by complex multicellular and multicytokine interactions. Its core mechanism involves retinal pigment epithelial (RPE) cells, glial cells, and inflammatory cells undergoing epithelial-mesenchymal transition (EMT), abnormal proliferation, migration, and contraction, ultimately leading to traction retinal detachment. Current treatment primarily relies on surgery, but faces limitations such as high postoperative recurrence rates and a lack of clinically approved effective adjuvant drugs. This review provides a comprehensive analysis of the PVR pathogenic network, integrating the roles of diverse cellular players with key signaling pathways. We place a particular emphasis on critically evaluating emerging therapeutic strategies, including targeted pathway inhibitors and, notably, innovative drug delivery systems, which represent a paradigm shift towards overcoming pharmacological barriers. By synthesizing mechanistic insights with translational applications, this article highlights current advances and underscores the gap between preclinical promise and clinical efficacy. It aims to serve as a timely resource for understanding the pathobiology of PVR and for guiding the development of future multi-targeted therapeutic interventions.